(untitled) (Journal of Humanities and Social Sciences Research, 2023)
Possession is a common grammatical feature across many languages, and the ways in which possession is marked and expressed can vary widely from language to language. In some languages, possession is marked by case, while in others, it is marked by the use of possessive pronouns or possessive affixes on nouns as in the English language. A possessor is a person or thing that has authority over the possessum. The term "possessive" may conjure up images of legal ownership, but the possessive relation encompasses more than just legal ownership. It includes any relationship that could exist between a possessor and a possessum, even if the similarities to the concept of ownership are superficial. This research is concerned with the syntax and pragmatics of possession in the short story Tea at Midland by David Constantine and its effect on the educational process. Two models are adopted to analyze possession: Syntactically speaking, this research paper deals with four types of possession, namely, Pre-nominal possession, Post-nominal possession, Double-oblique genitives, and Proper noun modifiers by KolKmann (2016). Pragmatically speaking, Stageberg’s (1981) six-type model of possession functions is adopted. The ultimate aim of this research paper is to prove that the author doesn’t use possession heavily in the story by chance; rather it is a matter of a stylistic choice to achieve his theme. The paper ends with a conclusion that possession is used on purpose in the story as a means to convey the theme and this reflects many pedagogical perspectives that can be derived from the interrelatedness between syntax and pragmatics.